The case of successful treatment of a patient with endobronchial intraluminal metastasis of kidney cancer - E. E. Fufaev; I. V. Dmitrochenko; I. I. Dzidzava; O. V. Barinov; D. A. Yasyuchenya; B. N. Kotiv; A. S. Sokolov; V. A. Popov (Вестник хирургии имени И.И. Грекова)
Tracheal cancer accounts for less than 0.2 % of the total number of oncological diseases. The medical literature describes isolated cases of metastatic lesions of the trachea and bronchi from distant organs. Metastasis of kidney cancer is observed most often in the absence of early detection of the tumor. We present a case of successful treatment of intraluminal metastasis of kidney cancer into the trachea.